Revitalization of Islamic Family Law Through the Management of Islamic Philanthropy Based on Zakat, Infaq, and Alms - Romi, Muhammad; Akbarizan, Akbarizan; Nurcahaya, Nurcahaya (STAINI Press, 2026)
This study examines the revitalization of Islamic family law through strengthening the management of Islamic philanthropy based on zakat, infaq, and sedekah (ZIS) in response to the increasing socio-economic challenges of modern Muslim families. The main problem lies in the weak implementation of family law, which is often influenced by economic conditions, such as alimony, divorce, and child protection. This study aims to analyze the strategic contribution of ZIS management in strengthening the function of Islamic family law. The research method uses a library study approach with content analysis of primary and secondary literature related to ZIS, family law, and national zakat regulations. The results show that ZIS plays a significant role in increasing family economic resilience, reducing the potential for domestic conflict, and strengthening the implementation of family law norms through measurable socio-economic support. Institutional integration between zakat institutions and religious courts has proven crucial for expanding access to assistance for vulnerable families and supporting fairer dispute resolution. The implications of this study include the urgency of strengthening ZIS governance and opportunities for further research on the digitalization model of synergy between zakat and religious courts in Islamic family law reform.